New Design Strategies for Truck Forebody Aerodynamics: A Pressure Contour and Velocity Streamline Analysis - Goh, Ching Pang (INTI International University, 2023)
The research focuses on the application of aerodynamics beyond aviation, particularly in heavy vehicle design. Traditionally associated with flight, aerodynamic principles play a vital role in minimizing drag for vehicles and trailers, as well as assessing wind stresses on various structures. Heavy vehicles, such as tractor-trailers and buses, consume a significant amount of fuel, and a substantial portion of this consumption is attributed to overcoming aerodynamic drag. The drag force acting on these vehicles increases fuel consumption, making it imperative to minimize drag to enhance fuel efficiency and reduce operational costs. Additionally, reducing drag can lead to improved stability, handling, and safety of heavy vehicles, further emphasizing the significance of aerodynamics in this context. The study provides a comprehensive overview of heavy vehicle aerodynamics, exploring the use of flow-control devices to reduce drag. Computational fluid dynamics (CFD) is employed to simulate the flow field around trucks, using a steady-state formula to evaluate the software's effectiveness in modeling contemporary truck aerodynamics. The primary objective is to enhance the aerodynamic profile of a truck's front end and reduce drag resistance through the implementation of an appropriate drag reduction system. This paper introduces five new designs to compare the drag coefficient, drag force, and fuel consumption with the benchmark design. The results show that Design 1 performs the best among all. The parameters used for comparison include the drag coefficient, drag force, and fuel consumption, which were analyzed using computational fluid dynamics simulations and steady-state formula evaluations. Furthermore, the study discusses future directions for advancing the field, emphasizing ongoing efforts to improve heavy vehicle aerodynamics and the broader implications for the transportation industry.